Effects of thermal histories on interfacial properties of carbon fiber/polyamide 6 composites: Thickness, modulus, adhesion and shear strength. (June 2016) - Li, Hongfu; Wang, Yang; Zhang, Chenwei; Zhang, Boming
Abstract: Interface thickness and modulus of carbon fiber (CF) reinforced polyamide 6 (PA 6) composites with different thermal histories are characterized as 331–394 nm and 0.24–0.30 times to fiber modulus, respectively. Transverse fiber bundle (TFB) test is firstly employed for evaluating semi-crystalline PA 6 interfacial adhesion. TFB Failure mechanisms are schematically given. Besides enhanced molecular entangling on fiber surface, increased matrix toughness is also found to have a great effect on improved TFB results. Droplet micro-debonding results show that decreasing cooling rate and increasing annealing temperature both decrease interfacial shear strength (IFSS) though residual PA 6 on carbon fiber surface increases. In the end, the above data are normalized together with some previous measured parameters. It shows that quenching of the CF/PA 6 composites and subsequent annealing are shown to give similar results as slow cooling. Relationships between each other are also discussed.